The development of sport and tourism in the Międzychód County and the concept of the European Green Deal - Poczta, Joanna; Styperek, Jarosław (Journal of Education, Health and Sport, 2022)
Sport and tourism may become one of the most important areas of the local economy of the four communes in the Międzychód district. Its areas are associated with the Międzychodzko - Sierakowskie Lake District, and the studies of the intensity of tourist traffic confirm this exactly. They show that guests’ stays in the region are mainly limited to visits to two tourist centers, the cities of Sieraków and Międzychód, and usually they are not long stays. The proposal for the development of sports and tourism in the Międzychód County is to increase the tourist traffic for sports tourism and extend the stay of tourists using the rich natural, cultural and landscape resources as well as agritourism infrastructure in rural areas. This idea is also guided by the inhabitants involved in the development of the region, representatives of local authorities, non-governmental organizations, cultural institutions, schools and entrepreneurs, therefore the main goal of the presented article is to find out about the opinion of the inhabitants of the Międzychód district on bicycle transport in the context of the European Green Deal.